APPLICATION OF THE FLOYD-WARSHALL ALGORITHM TO OPTIMIZE ELECTRICITY DISTRIBUTION IN THE CITY OF CIMAHI - Lusiani, Anie; Sartika, Euis; Suhartini, Ida; Nuryati, Neneng (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Efficiency in the use of electricity is a necessity for the sustainability of a better life. Almost all human activities utilize electrical energy, such as household appliances, industry, and even vehicles. This research contains the efficiency of electricity use in a housing by applying graph theory in optimizing the electricity distribution network system. The purpose of this study is to optimize the electricity distribution network system in the residential area of Kota Mas Cimahi, so that the best network model is obtained. Network data and information were obtained from PT. PLN UP3 Cimahi, West Java. The method used is to determine the minimum spanning tree in the electricity distribution network model by applying the Floyd-Wish algorithm. The initial model of the power grid was constructed by data on the position of substations and power poles, the number of power poles, and the length of the power cables connecting the poles. The data used is data on a line from several electricity distribution lines in this housing. The result of the minimum cable length on this line is 349 meters. The results of this study are expected to provide alternative solutions and additional information in planning and structuring the power grid optimally. Furthermore, the results of this research can also be used by PLN in order to support the government's program towards the efficiency of using electrical energy to serve the community because they get electricity services faster and cheaper